Comparison of Epidemiological Characteristics of Clinically Isolated ESBL and Non-ESBL Producing Escherichia coli from 2014 to 2022: A Single-Center Study - Wei Zhang; Qing Wang; Liru Zhang; Jiangxiong Wu; Jinlu Liu; Cheng Lu; Xinsheng Wang; Zhihua Zhang (Achievements and Challenges of Medicine and Medical Science Vol. 8, 2024)
Background: Over the years, the emergence and spread of extended-spectrum \(β\)-lactamase (ESBL)-producing E. coli strains have become a significant concern in clinical settings. Understanding the epidemiological characteristics of ESBL-producing E. coli isolates is crucial for effective infection control and antibiotic stewardship. Aim: This single-center study aims to investigate the epidemiological characteristics of clinically isolated Escherichia coli from 2014 to 2022. Methods: In vitro drug sensitivity of E. coli to 20 antibiotics was examined using the microbroth dilution method. A total of 7580 clinical E. coli strains were isolated from 2014 to 2022, among which 56.9% were identified as extended-spectrum beta-lactamase-producing strains. Drug susceptibility testing was performed using the broth microdilution method according to the guidelines provided by the Clinical and Laboratory Standards Institute (CLSI). The data were analyzed using the software WHONET5.6 and the R language platform. Results: The number of female patients exceeds that of males (4798 vs.2782), and the median age of females is higher than that of males. Over the study period, carbapenem resistance rates increased by more than 50% (2022 [1.34%] vs 2014 [0.8%]) and the annual number of isolates showed an upward trend (1264 in 2022 vs 501 in 2014). Drug resistance rates were the highest for penicillin (75–85%) and lowest for imipenem (1%). The resistance rate of strains isolated from male patients and sputum was found to be higher than that of female patients and urine, except for quinolones (p <0.05). The drug resistance rates from high to low were penicillins (75– 85%), tetracycline (64%), quinolones (64–67%), sulfamethoxazole (59.3%), cephalosporins (22–72%), aztreonam (34%), chloram-phenicol (21%), amikacin (2.8%), colistin (1.4%), meropenem (1.1%), and imipenem (1%). Urine, sputum, and blood accounted for 51%, 16.6%, and 10.6% of the samples, respectively. A greater number of female patients were included than male patients (4798[63.3%] vs 2782[26.7%]). Patients aged 50–80 accounted for 64.2% of those surveyed. Conclusion: Carbapenems remain the optimal choice for treating extended-spectrum beta-lactamase-producing E. coli infections (sensitivity rate: 98%). Colistin (87.7%) and amikacin (87%) exhibited good antibacterial activities against carbapenem-resistant E. coli. Long-term and continuous epidemiological surveillance of E. coli can facilitate the development of preventive strategies and control policies. In future research, bacterial genotyping has made a great contribution to the epidemiology of drug-resistant bacteria, and it should gradually become the mainstream monitoring method to be implemented.